THE CONCEPT OF DIDACTICS OF ELECTRICAL ENGINEERING - SERAFIN, Cestmir (Trends in education, 2015)
Electrical engineering is a traditional field, with whose products we meet at every step. In addition, our houses are lit and the heat, that it is pleasant to have a television, it is also great to have thanks to the computer the entire world at your fingertips. None of this we should not without experts electrical engineers. Their preparation is a matter of education in the system of vocational education, where the teaching of electrical items is focused on the acquisition of basic theoretical and practical knowledge, while on the theoretical knowledge immediately always follow practical exercises where the pupils having tried theoretical knowledge to specific examples. The definition of the training of teachers for the page field of teaching is an important part of the modern bond of the teacher, an expert in the given field.
Keywords: Subject didactics; electrical engineering; teaching; teacher professional subjects.